2016
DOI: 10.1016/j.appet.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Consumer trust in the Australian food system – The everyday erosive impact of food labelling

Abstract: Consumer trust in food system actors is foundational for ensuring consumer confidence in food safety. As food labelling is a direct communication between consumers and food system actors, it may influence consumer perceptions of actor trustworthiness. This study explores the judgements formed about the trustworthiness of the food system and its actors through labelling, and the expectations these judgements are based on. In-depth, semi-structured interviews with 24 Australian consumers were conducted. Theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 32 publications
1
52
0
1
Order By: Relevance
“…Strategies and policies that build consumer trust are not readily identifiable. Indeed, in addition to consumers not having complete information, trust is a complex phenomenon that does not depend only on rational judgments about risks, but involves both cognitive and emotional aspects (Tonkin et al, 2016a(Tonkin et al, , 2016b. Thus, literature is increasingly highlighting how improving consumer information and knowledge is not a very effective quick-fix to increase consumer trust (Eden et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Strategies and policies that build consumer trust are not readily identifiable. Indeed, in addition to consumers not having complete information, trust is a complex phenomenon that does not depend only on rational judgments about risks, but involves both cognitive and emotional aspects (Tonkin et al, 2016a(Tonkin et al, , 2016b. Thus, literature is increasingly highlighting how improving consumer information and knowledge is not a very effective quick-fix to increase consumer trust (Eden et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Returning to the discussion on how to influence trust levels, labelling has been identified by the literature as a way to affect 'consumer perceptions of trustworthiness' and to reinforce trust in the food system, even if interpretation of the labelled information may not necessarily remain strictly within the correct regulatory definition (Tonkin et al, 2016a(Tonkin et al, , 2016b.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in Europe, the United States, and Australia [4,12,13] have demonstrated that consumers have more confidence in elements of the food label that are regulated [13]. In Australia, the NIP is required on all packaged foods except those in very small packages.…”
Section: Discussionmentioning
confidence: 99%
“…Thus with very little relative personal control to manage perceived risks in practical terms (Dixon and Banwell, 2004), trust in the food system is essential. Food labelling is one of the primary methods of contact with the food system for most consumers (FSANZ, 2008) (see figure 1 for relevant definitions), with industry and government primarily seen as 'labellers', or the face of the food system (Tonkin et al, 2016). Thus gaining an understanding of how food labelling influences trust in food system actors is important.…”
Section: Introductionmentioning
confidence: 99%